People's Century 1900-1999 : the ordinary men and women who made the twentieth century. - Hodgson, Godfrey ([Place of publication not identified] : Times Books, 1996)
A companion to the PBS documentary series, People's Century is copiously illustrated, and the text, by veteran British journalist and historian Godfrey Hodgson, does a good job of documenting the colossal events of the century from the bottom up. Beginning with an essentially chronological approach that moves from World War I and the global depression onward to World War II and the cold war, the book transitions into a thematic organization, which covers such historical trends as movements against state racism, the international awareness of environmental problems, and the worldwide struggle for women's equal rights. Many personal stories humanize the sweeping themes and serve to make People's Century as entertaining as it is educational.
Keywords: History, Modern. -- 20th century -- Twentieth century; Civilization, Modern -- 20th century. -- Twentieth century